Negative association between resilience and event-related potentials evoked by negative emotion - Dan Chen (Nature Portfolio, 2018)
Abstract Individuals with low level of resilience are documented to be less capable of regulating negative emotion. To investigate the underlying neurophysiology, the present study examined the relationship between resilience and the late positive potential (LPP) evoked by emotionally negative pictures. Fifty-four participants watched negative and neutral pictures passively while their electroencephalogram (EEG) was recorded to assess LPP. Participants also completed the Connor-Davidson Resilience Scale (CD-RISC) for assessment of their resilience levels. We found that resilience was negatively correlated with the LPP response to negative emotional pictures. Additionally, this negative correlation was mainly driven by optimism, one of the three composite factors that contribute to resilience. Our results showed a neurophysiological correlate for the effect of resilience on negative emotion, and suggested a predictive value of optimism in identifying individuals potentially sensitive to affective interruptions.